Loss of vision secondary to obsessive-compulsive disorder: a case report - Torres, Albina Rodrigues [UNESP]; Domingues, Mariana de Souza; Shiguematsu, Alvio Isao [UNESP]; Smaira, Sumaia Inaty [UNESP] (Elsevier B.V., 2009)
Objective: To report a rare case of self-inflicted eye injury secondary to obsessive-compulsive disorder (OCD).Method: Case report.Results: A 41 year-old patient had significant bilateral visual loss and blunt trauma through touching his ocular cavities due to recurrent doubts regarding their shape and urges to check the format of bones and cartilages. Differential diagnosis with tic disorders is discussed, and the patient's treatment approach is described.Conclusion: Although rare, severe clinical complications can occur in OCD. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Obsessive-compulsive disorder; Compulsion; Self-mutilation; Self-inflicted eye injuries; Clinical complications